WHASA consensus document on the management of the diabetic foot - Liezel Naude; Hiske Smart; Lynne Tudhope; Gerda Janse van Rensburg; Howard Alexander; Talib Abdool-Carrim; Daniel Chrysostomou; Neford Ongaru; Hazem Al Dabbas; Monique Walker; Alison Lingard; Emma Trenholm; et al. (South African Family Practice)
No abstract available.